UPAYA KEMANDIRIAN DALAM PENYEDIAAN FLARE BAGI TEKNOLOGI HUJAN BUATAN - Haryanto, MSi, APU, Prof. Drs. Untung; Goenawan, R. D (Badan Pengkajian dan Penerapan Teknologi, 2009)
System production of small scale flare fabrication has been developed. System consist of three main apparatus ie. ball mill, compactor, and dryer oven. Products of flare have good quality on high performance of burning, long live of storage, and water resistant. Test particle after burning on BATAN laboratory shows that particles diameter range is 1.1 – 5.7 micron. This is the best spectrum of ultra giant nuclei to modifying warm cloud to enhance precipitation. The user of the flare production from this small scale fabrication is UPT Hujan Buatan BPPT, which will use for cloud seeding operasional base on flare device. This effort will strengththening the capability UPT Hujan Buatan on the selfempowerment on cloud seeding device production.